Stylistic Deceptions in Online News Journalistic Style and the Translation of Culture - Riggs, Ashley (Bloomsbury Academic, 2020)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. It is subject to a Creative Commons Attribution Non-Commercial No Derivatives Licence and funded by the Swiss National Science Foundation. This book demonstrates the central role played by the stylistic features of online news in constructing meaning and shaping cultural representations of people and places - in particular, France and Muslims/Islam. Taking the 2016 violent attack in Nice, France as a case study, Ashley Riggs analyses online news coverage of the attack from the UK, Spain, and Switzerland, three distinct linguistic and cultural spaces. An innovative mixed-methods approach, including content analysis and elements of translation criticism and comparative stylistics, is used to analyse this corpus, revealing the frequency and influence of stylistic devices found in online news and exploring how they help to shape reader interpretations. Drawing conclusions about journalistic practices by place and interrogating the notions of 'European identity' and 'European journalism', Stylistic Deceptions in Online News reveals how stylistic features may vary according to both political leanings and national and regional contexts, and the influence these features have upon readers.